Financial capability and financial literacy among university student - M. Razali, S. N. A. (Penerbit UTHM, 2018)
The statistics information by Department of Statistics Malaysia and the Ninth Malaysia Plan’s indicate that most youth group had declared bankrupctcy. As information given, it is showed that young Malaysians are not prepared to deal with the consequences of having financial crisis.The objectives of this study are to identify the level of student university financial literacy and financial capability and to analyze the relationship between the theory of planned behavior (TPB) factor and financial literacy toward financial capability among university student. Using description analysis and multiple linear regressions, it is found that there is lower level or incapable on the level of financial capability among the university students. Furthermore, the attitude, subjective norm and perceived behavior which are TBP factor had shown the relationship toward the level of financial capability.